Can Farmers’ Markets Supply Safe and Fresh Food to Urban Consumers in Dhaka? - Chanda, Debashish; Islam, Anowarul; Farhana, Ibrahim (CGIAR Initiative on Resilient Cities, 2024)
A farmers’ market is a weekly fresh market organized by farmers or their representatives, selling vegetables and fruits and other fresh foods directly to consumers. It is basically the establishment of a shorter value chain, and ideally only includes food grown safely, e.g., without harmful chemicals and with technical support from the local level staff of the Department of Agriculture Extension under the Ministry of Agriculture. The market establishes direct connection and ensures mutual benefits between farmers, consumers, and communities and thus ensures a win-win situation for all. Although these types of markets exist in many countries around the world, they were first established in Dhaka by the Dhaka Food System (DFS) project of the Food and Agriculture Organization of the United Nations (FAO). Six farmers markets under Dhaka North City Corporation were taken over by CGIAR’s Resilient Cities Initiative to continue after DFS project ended in December 2023. The markets were run through local government Wards and their councilors, staff of the City Corporations, and farmers groups to continue to operate and manage farmers' markets in their respective areas in the city. The aim was to shorten the value chain for quick food supply and to increase access to safe, nutritious, and fresh foods for local community residents in Dhaka North to develop direct linkages between producers and consumers without any type of middleman/group. After ending the DFS project and subsidized support to the markets, it was established that some of the markets were operating well, but some were not; 2 markets out of the 6 had stopped functioning. Some markets had strong support from Ward Councilors, Market Management Committee (MMC) and good operations strategies, but some markets have no adequate support from the Ward Councilor and MMC and weak strategies. The CGIAR Resilient Cities Initiative through the office of the International Potato Center (CIP), in partnership with FAO and Dhaka North City Corporation (DNCC), held stakeholders’ meetings and decided to continue to support the four functioning markets and aimed to reopen those two markets which were closed. Up to the present, CIP has been continuing to support and monitor regularly those four markets and both farmers and consumers are happy to have such fresh markets functioning again.